'Amazing Stories': Australian Newspapers and Anti-Spy Panic, 1910–1945©. Issue 4 (2nd October 2022) - Coatney Journalism Lecturer, Caryn
Abstract : Moral panic has become a popular concept to explain a media frenzy that has provoked public alarm. A largely unexplored area of panic has been the exceptional allegations of pro-Nazi secret agents in Australia during World War II. Moral panics have often been viewed as the outcome of the media acting as a single entity to generate wild reporting and mass hysteria. This article proposes a refinement of the concept by showing that the press published varied reporting about a government crackdown on so-called fascist spies. The article focuses on the British accused spy and self-proclaimed journalist, Adela Pankhurst, and John Curtin, a hard-hitting labour reporter who became Australia's wartime prime minister. Rival newspapers provided stylised expressions of civility and outrage about the sensational crackdown. The news of a battle against powerful traitors also shaped popular views of Curtin's leadership and Australia's need to uphold a democratic British identity.